Central Corneal Regularization – Optimization of Uncorrected Visual Acuity in Keratoconus Patients - Kaufmann, C.; Bochmann, F.; Baenninger, P.; Thiel, M. A. (Klinische Monatsblätter für Augenheilkunde, 2013)
Background: Combined excimer laser correction and corneal cross-linking is a promising concept in treating keratoconus patients. Central corneal regularization represents advanced topography-guided custom ablation for ectatic corneas, aiming at correcting irregular astigmatism and at increasing the optical regularity of the corneal surface.Patients and Methods: In a prospective single centre study, 10 keratoconus patients underwent combined treatment with corneal cross-linking and central corneal regularization by an iRES-Laser. Uncorrected visual acuity at 1 and 3 months postoperatively represented the primary endpoint.Results: Mean preoperative uncorrected decimal visual acuity was 0.15 (± 0.28 standard deviation). Mean postoperative visual acuity was 0.28 (± 0.47) at one month and 0.24 (± 0.25) at three months, respectively.Conclusions: Combined corneal cross-linking and central corneal regularization treatment has the potential to achieve a clinically significant improvement of uncorrected visual acuity.
Keywords: central corneal regularization; surface ablation; cross-linking; keratoconus